Attitudes of Computer Teachers on Twitter Network Towards Distance E-Learning During COVID-19 Pandemic - Alkhudairy, Monther Abdullah (Journal of Educational and Psychological Sciences, 2022)
The study aimed to determine the attitudes of computer teachers in the Twitter network towards distance e-learning during the Corona pandemic in the Kingdom of Saudi Arabia. The study used the qualitative analytical approach, by analyzing tweets in the Twitter network of (58) computer teachers, related to distance e-learning during teaching students computer subjects during the Corona pandemic, and the results revealed the presence of sentimental attitudes towards distance e-learning, Including positive attitudes from teachers, attitudes related to students’ interaction and enthusiasm, and teachers’ longing for face-to-face education, as well as cognitive attitudes, including attitudes related to the way the teacher teaches in virtual lessons synchronously or relying on Line lessons, in addition to behavioral attitudes, which are the contributions of teachers during the period of distance e-learning. The results of the analysis also reached the most prominent advantages of distance e-learning during the Corona pandemic, including solving vacation problems the absence of the teacher, acquiring technical and soft skills for students, and the absence of paperwork. The results also showed the most prominent problems of distance e-learning during the Corona pandemic from the point of view of computer teachers in the Twitter network, including technical problems, administrative problems and the practical application of computer subjects. The study recommended the necessity of establishing work teams in the Ministry of Education to monitor the interaction and opinions of education staff in the Twitter network to study the difficulties and problems they face, and to change the policies and regulations in the Ministry of Education to suit distance e-learning.